2013
DOI: 10.3102/1076998613494819
|View full text |Cite
|
Sign up to set email alerts
|

A Correlated Random Effects Model for Nonignorable Missing Data in Value-Added Assessment of Teacher Effects

Abstract: Value-added models (VAMs) are used by many states to assess contributions of individual teachers and schools to students' academic growth. The generalized persistence VAM, one of the most flexible in the literature, estimates the "value added" by individual teachers to their students' current and future test scores by employing a mixed model with a longitudinal database of test scores. There is concern, however, that missing values that are common in the longitudinal student scores can bias value-added assessm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 67 publications
(202 reference statements)
0
18
0
Order By: Relevance
“…However, as found by Herrmann et al (2013), results were inconclusive as to whether fixed or random approaches were preferable when the question of interest was the percentage of teachers who would shift from lowest to highest quintile, or vice versa, over 2 years. Karl, Yang, and Lohr (2013) found a correlated random effects model can be useful for investigating the impact of missingness on VA teacher rankings. In another study, Guarino, Reckase, and Wooldridge (2012) found that no estimation approach is better in all situations.…”
Section: Resultsmentioning
confidence: 99%
“…However, as found by Herrmann et al (2013), results were inconclusive as to whether fixed or random approaches were preferable when the question of interest was the percentage of teachers who would shift from lowest to highest quintile, or vice versa, over 2 years. Karl, Yang, and Lohr (2013) found a correlated random effects model can be useful for investigating the impact of missingness on VA teacher rankings. In another study, Guarino, Reckase, and Wooldridge (2012) found that no estimation approach is better in all situations.…”
Section: Resultsmentioning
confidence: 99%
“…That is, teacher effectiveness estimates in which data are missing at random compared to those in which data are not missing at random correlate at or above 0.98. In another study, Karl, Yang, and Lohr (2013) used flexible correlated random-effects models to jointly model student responses and missing data indicators. Their findings suggest that teacher rankings are sensitive to missing data under some models.…”
Section: The Impact Of Missing Datamentioning
confidence: 99%
“…Rizopoulos et al (2009) use this method to estimate the parameters of a joint model for a continuous longitudinal process and a time-todropout measurement. Karl (2012a) applies this approach to a multi-membership joint model. We will give a brief overview of the EM estimation procedure, and refer to Karl (2012a) for further details, as well as to Rizopoulos et al (2009) for similar calculations made in the setting of nested random effects.…”
Section: 2mentioning
confidence: 99%
“…We combine the FBS and FCS files, remove all games labeled "away", remove games between FCS and lower division teams, purge redundant neutral site games, add an indicator for games played between FBS and FCS schools, and remove the records of games played after the production of the final BCS rankings in each year. The processed data are available from Karl (2012b). See Table 12 in Appendix B for the first observations of our 2008 data set.…”
Section: Applicationmentioning
confidence: 99%